2016
DOI: 10.5535/arm.2016.40.6.989
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Step Activity During Task-Oriented Circuit Training in High-Functioning Chronic Stroke Survivors: A Proof-of-Concept Feasibility Study

Abstract: ObjectiveTo explore the amount of practice and progression during task-oriented circuit training (TOCT) in chronic stroke survivors; to test the use of pedometers and observation-based measures in detecting step activity; to verify the possible correlation between step activity and locomotor function improvements.MethodsSix community-dwelling chronic stroke survivors underwent 10 TOCT sessions (2 hours/each) over 2 weeks in which they were trained both on a treadmill and on six task-oriented workstations (W1–W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Ambulatory activity was operationally defined as the daily step count measured using a pedometer. In previous studies, ambulatory activity was assessed using a pedometer in patients with stroke, and this measurement method had an established feasibility, 19 , 20 , 21 validity, 22 , 23 and reliability. 23 We used a pedometer a with a 14-day data storage capacity that had a triaxial acceleration sensor that could measure daily steps.…”
Section: Methodsmentioning
confidence: 99%
“…Ambulatory activity was operationally defined as the daily step count measured using a pedometer. In previous studies, ambulatory activity was assessed using a pedometer in patients with stroke, and this measurement method had an established feasibility, 19 , 20 , 21 validity, 22 , 23 and reliability. 23 We used a pedometer a with a 14-day data storage capacity that had a triaxial acceleration sensor that could measure daily steps.…”
Section: Methodsmentioning
confidence: 99%
“…The use of robotic devices in murine models and human patients gives an unbiased evaluation of recovery of motor performances providing an accurate description of kinetic and kinematic aspects on motor performance during rehabilitation after stroke (Allegra Balasubramanian et al, 2010;Hogan and Krebs, 2011;Spalletti et al, 2014). Importantly, it is increasingly recognized that the combination of stimulation with physical rehabilitation synergistically creates a pro-plasticizing milieu where spared neurons are more susceptible to experience-dependent modifications (Alia et al, 2017;Straudi et al, 2016;Zeiler and Krakauer, 2013). To our knowledge, no investigation has yet described how the combination of optogenetic stimulation and motor training longitudinally molds cortical functional maps in the chronic phase after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with motor training, cortical stimulation creates a pro-plasticizing milieu where spared neurons are more susceptible to experience-dependent modifications 4,16,17 . Though several studies investigated the effect of combining neuronal modulation, such as TMS 1820 and tDCS 2123 , with robotic training, results are still contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that consumer‐based activity trackers are inaccurate in monitoring walking activity in slow walkers (<0.8 m/s) . In this context, one activity monitor has received particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies have revealed that consumer-based activity trackers are inaccurate in monitoring walking activity in slow walkers (<0.8 m/s). 11,12 In this context, one activity monitor has received particular attention. When the evaluated device is placed at the hip (as recommended by the manufacturer) in older healthy individuals walking slower than 0.8 m/s, its step error rate is higher than 10% 13 (ie, arbitrary threshold used previously and considered acceptable 14 ).…”
Section: Introductionmentioning
confidence: 99%